CORRELATION BETWEEN READING INTEREST AND INDONESIAN LANGUAGE LEARNING OUTCOMES TO THIRD GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN KLIRONG SUB-DISTRICT IN ACADEMIC YEAR OF 2019/2020 - Yunia Nur Arifah; Tri Saptuti Susiani; Ratna Hidayah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The study aimed to prove positive correlation between reading interest and Indonesian language learning outcomes to third grade students of public elementary schools in Klirong sub-district in academic year of 2019/2020 and to determine the contribution of reading interest to Indonesian learning outcomes to third grade students of public elementary schools in Klirong sub-district in academic year of 2019/2020. The research was quantitative correlational study. Sampling method was cluster random sampling technique using application of IBM SPSS Statistics version 23. The samples were 287 third grade students from twelve public elementary schools in Klirong sub-district. Data collection techniques were questionnaires and tests. Data analysis used correlation test with a significance level of 0.05 and adjusted R square. The correlation test showed Sig.= 0.000 (sig. <0.05). It meant that there was positive and significant correlation between reading interest and Indonesian learning outcomes. It indicated that that the higher reading interest, the higher Indonesian language learning outcomes and vice versa. Reading interest contributed 19.88% to Indonesian language learning outcomes.